Parenting and the Educational Performance of Secondary Schools Students’ in Rivers State, Nigeria - Udoinyang, Nathan; Ogbonnaya-Ngwu, Chidinma Esther (MultiTech Publisher, 2024)
This paper looks at parenting and the educational performance of secondary schools’ students’ in Rivers State, Nigeria. Survey methodology were employed to collect data from the population of all registered secondary school in Rivers State which was estimated as 3,467 as at 2023. Taro Yamane formula were used to arrive at a sample size of 400 and questionnaire was distributed of which 387 returned. With a mean criterion of 3.0, SPSS and Crombach Alpha coefficient of 0.05 were used to analyse the study's research topics. Reviewing the effect of parenting on the educational performance of secondary schools’ students’ in Nigeria we found out that absent of either father/mother from home, keeping children/wards in the hands of house help/care giver to take care of, family responsibility/obligation which made parents to show less concern in children/wards academic, devotion to work, lack of time, love, care, concern etc. are the effect of poor parenting that lead to poor academic performance of secondary school students River State, Nigeria. The study concluded that parent should try to involve themselves in their children/wards academics than just paying their fees, giving them good meals/snacks to school, buy whatever the children/ward’s needs, enrol them in expensive school then leave them in the hands of the teachers’ as academic involvement and child training is far beyond this knowing that they are their child/ward first teacher in life and also no one can train their child/ward better than they do knowing the fact that “charity begins at home”.